Estabilidade de membrana e microscopia de força atômica em eritrócitos de voluntárias de diferentes idades - Freitas, Mariana Vaini de (2013)
CHAPTER II: Objective: To evaluate the influence of age on the relationships between biochemical and hematological variables and stability of erythrocyte membrane in relation to the sodium dodecyl sulfate (SDS) in population of 105 female volunteers between 20 and 90 years. Methods: The stability of RBC membrane was determined by non-linear regression of the dependency of the absorbance of hemoglobin released as a function of SDS concentration, represented by the half-transition point of the curve (D50) and the variation in the concentration of the detergent to promote lysis (dD). Results: There was an age-dependent increase in the membrane stability in relation to SDS. Analyses by multiple linear regression showed that this stability increase is significantly related to the hematological variable red cell distribution width (RDW) and the biochemical variables blood albumin and cholesterol. Discussion: The positive association between erythrocyte stability and RDW may reflect one possible mechanism involved in the clinical meaning of this hematological index. CHAPTER III: Objective: To associate the morphological characteristics of erythrocytes obtained by atomic force microscopy (AFM) with its membrane stability and biochemical and hematological parameters in volunteers between 20 and 90 years. Methods: Contact-mode AFM provided arithmetic mean roughness (Ra), maximum height (Rz), average height (Rp) and average depth (Rv) of the cell membrane, as well as width, height and depth of the erythrocyte image. The sigmoidal curve of hemolysis by sodium dodecyl sulfate (SDS) was used to obtain the stability variables given by the half-transition point (D50) and the variation in the SDS (dD) concentration necessary to promote complete hemolysis of the blood samples. The microscopy and stability data were correlated with hematological and biochemical variables and antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT) of each volunteer. Results: The values of Ra were lower in the group of older volunteers and presented inverse correlations with D50 and non-HDL- and total cholesterol. The Cat activity presented an inverse correlation with Amax, triglycerides and VLDL-cholesterol, while the SOD activity exhibited a direct correlation with the erythrocyte width. Discussion: The smaller values of Ra found in the older volunteers erythrocytes may be related to the membrane changes caused by high values of blood cholesterol and decreased activities of antioxidant enzymes.